DEVELOPMENT OF â€œISAYHEARTâ€ MOBILE APPLICATION TO MONITOR HEALTH DATA AMONG GENERAL POPULATION IN MALAYSIA - Abdul Hapes Mohammed; Muhammad Hakimi Ahmad; Norfiza Ibrahim; Nadia Abdul Wahab (Journal of Islamic, Social, Economics and Development, 2022)
The development of mobile health applications has gotten a lot of attention recently,with some researchers referring to it as the future of healthy living. These mobile health appsserve as an alternative to traditional health monitors. Because most smartphones at presentcome with advanced sensors and technology, they can be utilized for a variety of purposes andservices. These apps could be used almost anywhere and at any time. Nonetheless, many peopleare unaware of this advancement due to a lack of knowledge and exposure of mhealth. The goalof this study is to create a mobile health software that can be utilized by Malaysian, regardlessof their age and location. Without the presence of a doctor or medical aid, the mobileapplication allows users to track and monitor their health. Therefore, it is essential to make useof this new rising technology to create a mobile health application that promotes mHealth inMalaysia. Planning, requirement analysis, design, development, testing and maintenance, anddocumentation are the six phases of the Agile Methodology that is used to guide this study. TheGoogle Android Studio is used in the design and development of the mobile application. Amongthe features of this mobile application are a body mass index (BMI) calculator, vital scans,nearest hospitals, and articles search. The evaluation of the mobile application is done by usingUser Acceptance Test. The results reveal that most of the participants feels that this applicationhas a good usability and they feel satisfied with this application as technology is so readilyavailable, creating a mobile health application system can benefit the community by giving acost-effective tool for monitoring and tracking their health.